Miquelianin and spiraeoside from Filipendula ulmaria mitigate α-synuclein accumulation in C.elegans and reduce the expression of neuroinflammatory cytokines in human microglia - Redl, Martina; Weisenburger, Sabrina; Wasilewicz, Andreas; Grienke, Ulrike; Lehner, Martin D.; Bredenbröker, Dirk; Rollinger, Judith M. (Frontiers in Pharmacology, 2026)
IntroductionChronic neuroinflammation and impaired proteostasis are increasingly recognized as interconnected drivers of Parkinson’s disease (PD). Due to their pleiotropic character, multicomponent herbal remedies combining anti-inflammatory and proteostatic activity may counteract these disease-promoting processes. This study investigated a hydroethanolic extract of Filipendula ulmaria (FE) for its ability to modulate neuroinflammation, proteostasis, and aging-associated mechanisms relevant to PD.MethodsThe effects of FE on lifespan and health span were assessed in wild-type and on α-syn::YFP fluorescence, survival and thermoresistance in transgenic NL5901 Caenorhabditis elegans. FE was fractionated by flash chromatography, and bioactivity was assigned to individual constituents using LC-MS dereplication and a 1H NMR-based biochemometric approach. Identified constituents were further examined for their capacity to reduce α-syn::YFP fluorescence and enhance thermotolerance in NL5901. To assess their relevance in neuroinflammation, all samples were examined in LPS-stimulated human microglial HMC3 cells for their effects on pro-inflammatory gene expression.ResultsFE extended lifespan, improved health span and reduced α-syn::YFP fluorescence in NL5901 by up to 25% at 200 μg/mL. In HMC3 cells, FE significantly downregulated IL-1β, IL-6, and MCP-1 expression at 100 μg/mL without cytotoxicity. Biochemometric and LC-MS analyses identified the flavonoid glycosides spiraeoside and miquelianin as key constituents, reducing the α-syn::YFP fluorescence by 32% and 35% at 200 μg/mL, respectively, while simultaneously increasing thermotolerance in NL5901 and suppressing pro-inflammatory cytokine expression in microglia.ConclusionsFE represents a promising source of neuroprotective agents targeting both neuroinflammation and proteostasis, supporting spiraeoside and miquelianin as hit candidates for preventive strategies against early neurodegenerative mechanisms.